The Effects of Resonance Frequency Breathing on Cardiovascular System and Brain-Cardiopulmonary Interactions - Wang, Xiaoni; Nie, Jingli; Lu, Yuchen; Zhang, Haoyu; Zhang, Jianbao (Applied psychophysiology and biofeedback, 2025)
Resonance frequency (RF) is characterized as the specific frequency at which a system, equipped with delayed self-correction or negative feedback mechanisms, exhibits maximal amplitude oscillations in response to an external stimulus of a particular frequency. Emerging evidence suggests that the cardiovascular system has an inherent RF, and that breathing at this frequency can markedly enhance health and cardiovascular function. However, the efficacy of resonance frequency breathing (RFB) and the specific responses of the cardiovascular, respiratory, and central nervous systems during RFB remain unclear. In this study, we recruited 27 healthy young male subjects (aged 20–30 years) and used the corrected sliding method to accurately determine each subject’s RF. We then investigated cardiovascular activity, cardiorespiratory coupling, and the brain-cardiovascular network to clarify the effects and mechanisms associated with RFB. Our results indicate that: (a) the corrected sliding method can precisely evaluate RF; (b) the reduction in blood pressure is unique to RFB and not observed in other slow-paced breathing patterns (RF + 1 and 6 breaths per minute), which we attribute to the α-wave and parasympathetic-BRS pathway; (c) during slow-paced breathing, cardiorespiratory coupling predominantly favors the respiration-to-heart direction, with the RF stage eliciting the most significant response, while brain-cardiopulmonary information transfer increases across all tasks. These findings offer valuable insights into the impact of RFB on the cardiovascular, respiratory, and central nervous systems, potentially laying the groundwork for future research to optimize respiratory training protocols and improve health outcomes.